1994
DOI: 10.1021/j100098a032
|View full text |Cite
|
Sign up to set email alerts
|

Sorbate Immobilization in Molecular Sieves. Rate-Limiting Step for n-Hexane Uptake by Silicalite-I

Abstract: Sorption uptake of hydrocarbons by molecular sieves with nonuniform micropore systems such as MFI-type zeolites may be governed by a complex of mechanisms instead of pure intracrystalline diffusion. In the particular case of sorption kinetics of n-hexane on silicalite-I, processes occur on the microcrystal level which comprise both Fickian diffusion and sorbate immobilization/mobilization. The rate processes connected with the immobilization of the sorbing species are due to both geometrical constraints and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Frequency Response [8] and Square Wave [9] methods have been used to measure the decrease in the diffusivity for n-hexane in silicalite with loading, which is in agreement with the results obtained by Micke et al from the sorption uptake kinetics [10]. The nhexane diffusivity in silicalite-1 reported therein is independent of concentration, but a linear concentration dependence was found for the self-diffusivity.…”
Section: Introductionsupporting
confidence: 85%
“…Frequency Response [8] and Square Wave [9] methods have been used to measure the decrease in the diffusivity for n-hexane in silicalite with loading, which is in agreement with the results obtained by Micke et al from the sorption uptake kinetics [10]. The nhexane diffusivity in silicalite-1 reported therein is independent of concentration, but a linear concentration dependence was found for the self-diffusivity.…”
Section: Introductionsupporting
confidence: 85%
“…has been used to describe the isotherm for n-hexane (Micke et al, 1994;Song and Rees, 1997). As can be seen from Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has for example been reported that an immobilization term has to be considered to obtain a correct description of the n-hexane diffusion in ZSM-5. 11,12 In this work, we will study the adsorption of linear alkanes in ferrierite (FER), which has a pore structure consisting of intersecting channels and cages. We will focus on the possible existence of chain length effects in this system that will affect both the adsorption and diffusion properties.…”
Section: Introductionmentioning
confidence: 99%